ABSTRACTS OF PRESENTED PAPERS FROM THE 58TH ANNUAL CONVENTION OF THE PARAPSYCHOLOGICAL ASSOCIATION JOINT WITH THE 39TH INTERNATIONAL ANNUAL CONVENTION OF THE INCORPORATED SOCIETY FOR PSYCHICAL RESEARCH, GREENWICH UNIVERSITY, LONDON, UNITED KINGDOM, JULY 16-19, 2015 (Journal of Parapsychology)
The article presents parapsychology abstracts, featured at the 58th Annual Convention of the Parapsychological Association and the 39th International Annual Convention of the Incorporated Socity for Psychical Research, including parapsychology, paranomal activities and unidentified flying objects.